Combatting Terrorism at SEA: Assessing NATO’S Maritime Operations in the Mediterranean (Journal of International Studies, 2019)
Terrorism via Mediterranean Sea route is one of the security threats faced by Europe in recent years. The basin recorded large volume of maritime vessels traversing daily via the major straits and consequently expose them for the possibility of terrorist attacks. This includes cargo and commercial vessels that carry tons of valuable cargo. There is growing concern that the vessels may be used to support terrorist activities. In light of this, NATO has adopted maritime operations to strengthen sea patrolling and enhance security of sea lanes in the Mediterranean. This paper seeks to examine the terrorist incidents occurred in the Mediterranean Sea. The paper then scrutinizes the evolution of NATO’s approaches to combat terrorism in the basin from 2001 until 2016. Specifically, this paper analyses the implementation of Operation Active Endeavour (OAE) which has initiated as an immediate response to the 9/11 terrorist attacks in the United States to fight against international terrorism. The mandate assigned through this operation includes, amongst others, monitoring and surveillance activities, escorting assistance, compliant boarding and joint training with NATO partners. These tasks have significantly contributed to a sharp decline in terrorist plot in the Mediterranean Sea. This paper obtains its data from textual analysis and interviews with NATO military officers. The results conclude that maritime operations by NATO play a functional role to hinder the potential of terrorist attacks and effectively maintain the security of the sea lanes.